The first prejudice : religious tolerance and intolerance in early America - Grenda, Christopher S.; Beneke, Chris (Christopher J.) (Early American studies., 2011)
Leading religious historians connect changes in law and rhetoric to daily cooperation and conflict in early America. These essays examine such topics as Native American spiritual life, the biblical sources of tolerance and intolerance, contemporary philosophies of religious liberty, and the resilience of African American faiths.